Fractionated Extracts From Gnidia kraussiana (Malvales: Thymeleaceae) as Bioactive Phytochemicals for Effective Management of Callosobruchus maculatus (Coleoptera: Chrysomelidae) in Stored Vigna unguiculata (Fabales: Fabaceae) Seeds. Issue 1 (15th February 2021) - Kosini, D; Nukenine, E N; Agbor, G A; Tchinda, A T; Abdou, J P; Yaya, J A G; Kowa, T K
Abstract: One of the most important global problems is protecting food from insect pests. The negative effects of synthetic insecticides on human health led to a resurgence of interest in botanical insecticides due to their minimal ecological side effects. Therefore, the insecticidal potential of hexane, acetone, and methanol extracts of Gnidia kraussiana Meisn roots at 1 and 5g/kg, and neem seed oil (NSO), used as standard insecticide, were evaluated. Ovicidal and larvicidal toxicity was tested by treating freshly laid eggs and larvae at different immature stages of Callosobruchus maculatus (F.). Cowpea ( Vigna unguiculata ) (L.) Walp seed damage and weight loss were assessed after a storage period of 4 mo. Repellency effects were detected in choice test using a linear olfactometer. All the fractions were toxic to C. maculatus ; however, their bioactivities were inversely correlated with products polarity. Extracts proved to be more toxic than the commercial NSO. The acetone extract was more effective against immature stages of C. maculatus than the methanol extract; eggs, first-, and second-instar larvae being the more susceptible. No cowpea seed damage and weight loss were recorded from the seeds treated with hexane and acetone extracts at the dosage of 5 g/kg, after 4 mo of storage. Extracts evoked stronger repellency effects compared with the tested standard insecticide. According to the above, hexane and acetone extracts are good candidates for incorporation in integrated pest management programs for the control of C. maculatus in stored cowpea seeds. Graphical Abstract: